Do the Eyes Have It? A Systematic Review on the Role of Eye Gaze in Infant Language Development - Çetinçelik, Melis; Rowland, Caroline F.; Snijders, Tineke M. (Frontiers in Psychology, 2021)
Eye gaze is a ubiquitous cue in child-caregiver interactions and infants are highly attentive to eye gaze from very early on. However, the question of why infants show gaze-sensitive behavior, and what role this sensitivity to gaze plays in their language development, is not yet well-understood. To gain a better understanding of the role of eye gaze in infants’ language learning, we conducted a broad systematic review of the developmental literature for all studies that investigate the role of eye gaze in infants’ language development. Across 77 peer-reviewed articles containing data from typically-developing human infants (0-24 months) in the domain of language development we identified two broad themes. The first tracked the effect of eye gaze on four developmental domains: (1) vocabulary development, (2) word-object mapping, (3) object processing, and (4) speech processing. Overall, there is considerable evidence that infants learn more about objects and are more likely to form word-object mappings in the presence of eye gaze cues, both of which are necessary for learning words. In addition, there is good evidence for longitudinal relationships between infants’ gaze following abilities and later receptive and expressive vocabulary. However, many domains (e.g. speech processing) are understudied; further work is needed to decide whether gaze effects are specific to tasks such as word-object mapping, or whether they reflect a general learning enhancement mechanism. The second theme explored the reasons why eye gaze might be facilitative for learning, addressing the question of whether eye gaze is treated by infants as a specialized socio-cognitive cue. We concluded that the balance of evidence supports the idea that eye gaze facilitates infants’ learning by enhancing their arousal, memory and attentional capacities to a greater extent than other low-level attentional cues. However, as yet, there are too few studies that directly compare the effect of eye gaze cues and non-social, attentional cues for strong conclusions to be drawn. We also suggest there might be a developmental effect, with eye gaze, over the course of the first two years of life, developing into a truly ostensive cue that enhances language learning across the board.